Proceedings of the International Conference on High Performance Computing, Networking, Storage and Analysis 2013
DOI: 10.1145/2503210.2503256
|View full text |Cite
|
Sign up to set email alerts
|

Enabling fair pricing on HPC systems with node sharing

Abstract: Co-location, where multiple jobs share compute nodes in large-scale HPC systems, has been shown to increase aggregate throughput and energy efficiency by 10 to 20%. However, system operators disallow co-location due to fair-pricing concerns, i.e., a pricing mechanism that considers performance interference from co-running jobs. In the current pricing model, application execution time determines the price, which results in unfair prices paid by the minority of users whose jobs suffer from co-location.This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…We rely on the presence of an admission control system that chooses VM placement across the data center [Chen et al 2012;Schwarzkopf et al 2013], and we assume that the hypervisor supports live migration [Jo et al 2013] in case a node becomes overloaded. While both VM placement and migration present open questions for research, AutoPro focuses on a different challenging and interesting problem: automating allocation of a contended resource within a single node, based on application-level performance SLOs.…”
Section: Automated Fine-grained Provisioningmentioning
confidence: 99%
See 1 more Smart Citation
“…We rely on the presence of an admission control system that chooses VM placement across the data center [Chen et al 2012;Schwarzkopf et al 2013], and we assume that the hypervisor supports live migration [Jo et al 2013] in case a node becomes overloaded. While both VM placement and migration present open questions for research, AutoPro focuses on a different challenging and interesting problem: automating allocation of a contended resource within a single node, based on application-level performance SLOs.…”
Section: Automated Fine-grained Provisioningmentioning
confidence: 99%
“…To deal with the second issue, the provider could employ techniques to limit performance degradation [Mars et al 2011;Govindan et al 2011] and, when this is not enough, to estimate the extent of the performance degradation [Breslow et al 2013;Dwyer et al 2012] and scale the bill accordingly.…”
Section: Billing Schemementioning
confidence: 99%
“…ing the low use of a node's memory and underutilization of a node's CPU resource [1]- [3]. Consequently, various cluster scheduling algorithms (such as POPPA [4], DFRS [5]) and backfilling algorithms [6]- [8] have been developed to allow multiple jobs to coexist on the same node to improve overall turn-around times and fairness, which leads to improving the utilization of HPC systems. Trends for HPC workload point toward diversity.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach prevents jobs from different users from clobbering one another, it leads to a missed performance opportunity. In fact, recent work has shown that colocation, where a set of jobs from different users runs 1 This paper received a nomination for the Best Paper Award at the SC2013 conference and is published here with permission of ACM, see [12]. Also, the paper was nominated for the Best Student Paper Award.…”
Section: Introductionmentioning
confidence: 99%